Equine Endothelial Cells Support Productive Infection of Equine Infectious Anemia Virus - Maury, Wendy (American Society for Microbiology, 1998)
Previous cell infectivity studies have demonstrated that the lentivirus equine infectious anemia virus (EIAV) infects tissue macrophages in vivo and in vitro. In addition, some strains of EIAV replicate to high titer in vitro in equine fibroblasts and fibroblast cell lines. Here we report a new cell type, macrovascular endothelial cells, that is infectible with EIAV. We tested the ability of EIAV to infect purified endothelial cells isolated from equine umbilical cords and renal arteries. Infectivity was detected by cell supernatant reverse transcriptase positivity, EIAV antigen positivity within individual cells, and the detection of viral RNA by in situ hybridization. Virus could rapidly spread through the endothelial cultures, and the supernatants of infected cultures contained high titers of infectious virus. There was no demonstrable cell killing in infected cultures. Three of four strains of EIAV that were tested replicated in these cultures, including MA-1, a fibroblast-tropic strain, Th.1, a macrophage-tropic strain, and WSU5, a strain that is fibroblast tropic and can cause disease. Finally, upon necropsy of a WSU5-infected horse 4 years postinfection, EIAV-positive endothelial cells were detected in outgrowths of renal artery cultures. These findings identify a new cell type that is infectible with EIAV. The role of endothelial cell infection in the course of equine infectious anemia is currently unknown, but endothelial cell infection may be involved in the edema that can be associated with infection. Furthermore, the ability of EIAV to persistently infect endothelial cultures and the presence of virus in endothelial cells from a long-term carrier suggest that this cell type can serve as a reservoir for the virus during subclinical phases of infection.